Market value of R&D, patents, and CEO characteristics - Lipeng Wang; Thanos Verousis; Mengyu Zhang (Financial Innovation, 2025)
Abstract The contribution of knowledge capital to firm value has increased significantly, from 25% in the 1970s to 45% in the 2010s (Belo et al. in Decomposing firm value J Financ Econ 143:619–639, 2022). However, what influences firms’ ability to maximize the effect of knowledge capital on firm value? Drawing on insights from upper echelons, agency, and behavioral agency theories, we show that CEO characteristics are crucial in enabling firms to take advantage of knowledge stock. We empirically demonstrate that short-term CEO compensation structures are detrimental to a firm’s ability to take advantage of its knowledge stock. We further show that CEO power enhances knowledge stock and R&D intensity. Our study provides direct empirical evidence of the importance of CEO compensation structure and corporate governance in understanding firm value in a knowledge economy.